inggris - Aulia, Rosyada Dinda; Prabayanti, Herma Retno (The Commercium, 2024)
This research aims to analyze consumer reception of live streaming on the TikTokShop animal and plant account. TikTok social media is one of the most popularplatforms for users around the world, including Indonesia, which is ranked secondin number of users after America. TikTok Shop is a new innovative feature inIndonesia that provides business opportunities for entrepreneurs to promote theirproducts. However, strict regulations regarding the sale of animals and plants onthe TikTok Shop pose challenges for business owners. This research aims tounderstand how consumers respond and interpret the content presented by sellersin TikTok Shop live streaming. This research uses a qualitative reception analysisapproach using the AIDA model and persuasive communication theory. The resultsof this research are that consumers on TikTok are in a dominant position despitestrict regulations, but feel they agree with the policy. As for consumers who are in anegotiating position, consumers feel doubtful due to the regulations on TikTok, butconsumers feel confident after interacting with sellers via live streaming sales.